THE USE OF ART AND CULTURE BY POLITICS IN A TOTALITARIAN STATE. (ALBANIA) - Mullahi, Anila (European Scientific Journal, ESJ, 2014)
From ancient times up to contemporary the subjective and affective aspect of literature has been considered to be subtle aspects, but at the same time the most important mean to achieve and retain the power. The political power that came into force in Albania, after 1944, as any other authoritarian power, used the aesthetics as a mean to control the masses. The relation of aesthetics to politics, in these times can be seen through a twofold point of view: On one hand there is the politicizing of art and on the other hand the struggle to aestheticize the politics. The writer and the artist in general was not any more an individual with a specific education, or with a notable culture or talent. The artist was anyone who was sufficiently indoctrinated and was to some extents talented, and who could put on the ideology an artistic veil. By employing as a base the deformation of the aesthetical and philosophical ideas of Hegel, which mystify and instrumentalize art as a didactic and moral mean, art was actually used as an effective mean of propaganda. The publishing of literary periodicals, opening exhibitions, giving prices etc., were all activities which aimed to create the idea that art had a quantitative and qualitative improvement and that it even was in the boarders of geniality. In reality the art of this epoch, was mainly an artistic mediocrity, but a very effective propaganda. Many artists, who were apprised for their art, actually were praised for the effective propaganda in their works.